Security in Wireless Sensor Network (WSN): A Detailed Survey - Dr. Amit K. Agarwal, Ankur Sirohi (International Journal of Advanced Science and Technology, 2020)
Wireless sensor network employs small devices (or sensors) with constrained abilities to sense, gather, and distribute the data in various real-world scenarios. Since these networks become broad-opened, security`s issues become a primary interest, particularly in assignments for mission-critical. In this paper, threats to sensor to sensor`s networks and vulnerabilities are identified. Then a summary for security`s concern is provided. These concerns are then classified into 7 classes namely attacks identification (or detection) and prevention, cryptography, key management, physical security, secure information fusion, secure routing and different security issues. Simultaneously the advantages and dis-advantages of modern security schemes in each category are analysed. Moreover, different approaches and methods which are used. In these categories are also summarized in the paper.